The Effect of Inflation and Exchange Rate on the Jakarta Composite Index (JCI) at the Indonesia Stock Exchange (IDX) - Eva Fadilah; Enji Azizi (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
This research seeks to examine the impact of inflation and exchange rates on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange (IDX) from 2019 to 2024. The study uses secondary monthly data for inflation, exchange rates, and the JCI, which were sourced from the official websites of Bank Indonesia and IDX. A quantitative approach is employed, utilizing multiple linear regression analysis along with classical assumption tests and both simultaneous and partial hypothesis testing. The findings reveal that, individually, both inflation and exchange rates have a significant effect on the JCI. When analyzed together, inflation and exchange rates also significantly influence the JCI. These results underscore the importance of macroeconomic stability, particularly the stability of the rupiah exchange rate, in shaping stock market trends in Indonesia. The study suggests that fluctuations in the inflation rate and the exchange rate can lead to uncertainty in the stock market, impacting investor decisions and market performance. These findings are particularly relevant in the context of Indonesia’s open economy, where external factors and global economic conditions can also influence domestic financial markets. This research aims to offer valuable insights to investors, policymakers, and academics, helping them understand how key macroeconomic variables, such as inflation and exchange rates, influence the dynamics of the capital market. The study emphasizes the need for maintaining economic stability to foster a conducive environment for market growth and investor confidence. By analyzing these macroeconomic factors, the study provides a clearer understanding of their role in stock market performance and offers a foundation for future research and policy development in the Indonesian financial market. Additionally, the results of this research could serve as a basis for further studies that explore the relationship between macroeconomic factors and stock market behavior in emerging markets.